A Study on The Semantics of Opposite Compounds in Modern Chinese - Xingyu, Huo (Mandarinable: Journal of Chinese Studies, 2024)
In modern Chinese, many words are composed of a pair of morphemes with opposite meanings, such as "左右(left and right)", "褒贬(commendatory and derogatory)", which constitutes an important phenomenon in the field of lexicology. Although the number of opposite compounds is limited, the study of their lexicalization process and cognitive mechanism is of great significance for expanding the research results of modern Chinese lexicology. In addition, the application of opposite compounds in teaching, especially in teaching Chinese as a foreign language, poses challenges and needs to be further studied. In this study, the opposite compounds in the Modern Chinese Dictionary (7th edition) were investigated. According to the relationship between word meaning and morpheme meaning, 260 opposite compounds were divided into three categories: "word meaning = morpheme meaning", "word meaning > morpheme meaning" and "word meaning ≠ morpheme meaning". By analyzing word frequency in a corpus, this study explored the correlation between semantic integration and frequency of opposite compounds. The significance of this work lies in enriching the corpus resources for studying antonymic compounds, solving issues related to meaning and morpheme classification, which enhances existing research and deepens its content. Additionally, it provides pedagogical guidance for teaching Chinese as a second language, aiding learners in mastering antonymic compounds more easily.